Qur'anic Conceptions of Knowledge and Contemporary Islamic Educational Praxis: Exegesis of QS. Al-Mujadilah 58:11 and QS. Al-Fathir 35:28 - Munjahid, Munjahid; Latansa, Andressa Muthi’ (Darul Yasin Al Sys, 2026)
This study clarifies terminological distinctions among ‘ilm, science, and knowledge across Western, Arabic, and Indonesian scholarly traditions and examines the pedagogical implications of QS. Al-Mujadilah (58:11) and QS. Al-Fathir (35:28) for Islamic education in Indonesia. A qualitative literature review with narrative synthesis was employed, drawing on classical tafsir, Arabic lexica, contemporary exegesis, philosophy of science, policy documents, and peer-reviewed research in Arabic, English, and Indonesian. Reflexive thematic synthesis generated three convergent findings. First, Western and Arabic traditions distinguish structured scientific products, practices or methods, and general knowledge, whereas Indonesian usage often conflates these meanings. Second, the two Qur’anic verses emphasize an integrative ideal that links iman, ‘ilm, and ethical conduct, highlighting social responsibility and the elevated status of knowledgeable believers. Third, these conceptual and scriptural resources support an integrative, contextual, and multidisciplinary model of Islamic education. The study proposes an operational orientation of ‘ilm as epistemically rigorous, ethically grounded, and socially engaged. It concludes that Islamic education in Indonesia should strengthen curricular integration between Qur’anic values, contemporary sciences, and digital literacy; enhance teacher professionalization and inclusive accreditation; and develop interdisciplinary training supported by collaborative research ecosystems. These findings contribute to Islamic educational thought by offering a conceptually grounded framework for aligning Qur’anic epistemology with contemporary educational reform, while also identifying the need for future empirical evaluation of the proposed reforms.